THE EFFECT OF CORN BRAN REPLACEMENT WITH FERMENTED BREAD WASTE IN RATION ON THE CARCASS COMPOSITION OF MALE BALI DUCKS (Anas sp.) - I G. R., Ermawan; Siti, N. W.; Puspani, E. (Jurnal Peternakan Tropika, 2021)
fermented bread waste in ration on the carcass composition of male bali ducks (Anas sp.). The research was conducted at the Farm Faculty of Animal Science, Udayana University for 8 weeks. The research used was a completely randomized design (CRD) with 3 treatments and 5 replications, so there were 15 experimental units. Each experimental unit used 3 ducks with a weight range of 50±2 grams. The three treatments were ration without bread waste (Treatment P0), (Treatment P1) ration of 50% corn bran raplanced with fermented bread waste and (Treatment P2) ration that 100% corn bran replaced with fermented bread waste. Variable observed were slaughter weight, carcass weight, carcass percentage, and carcass physical composition including bone, and fat. The results showed that the P1 and P2 treatments were able to increase the slaughter weight by 7.22% and 14.54% and were able to increase the carcass weight by 7.22% and 15.94% compared to control, but these treatments were not able to increase the percentage of meat, the percentage of carcass, percentage of bone, and percentage of fat male bali ducks ( Anas sp .). Based on the results of the study, it can be concluded that the replacement of corn bran in the ration with fermented bread waste flour on the physical composition of the carcass of male Bali ducks (Anas sp .) as much as 100% of bread waste flour has not been able to increase the physical composition of the cut weight and carcass weight, but it has no effect on the physical composition of the carcass of male Bali ducks ( Anas sp .).   Keywords : male bali duck (Anas Sp.), appearance, bread waste